Preparation and modification method and application of electro-catalytic material of Cu-MOF

By introducing the ionic liquid [EMIM][BF4] modification on the Cu3(BTC)2 catalyst, the [EMIM][BF4]@Cu3(BTC)2 catalyst was formed, and the problems of high potential, difficulty in activation and poor selectivity of Cu-based catalysts in the electrocatalytic CO2 reduction process were solved, which significantly improved the Faraday efficiency of ethylene.

CN119800438APending Publication Date: 2025-04-11ZHEJIANG UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510022331.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In the electrocatalytic CO2 reduction process, existing Cu-based catalysts have problems such as excessive potential, difficulty in activation, poor selectivity of target products, low Faraday efficiency, and competition in hydrogen evolution reaction.

Method used

By introducing the ionic liquid [EMIM][BF4] to modify Cu3(BTC)2 to form the [EMIM][BF4]@Cu3(BTC)2 catalyst, the advantages of the ionic liquid are used to improve the catalytic performance.

Benefits of technology

The modified catalyst exhibits higher ethylene selectivity and Faraday efficiency at -2.04V vs Ag/AgCl voltage, with the Faraday efficiency of ethylene more than doubled.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800438A_ABST
    Figure CN119800438A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation modification method and application of a Cu-MOF electro-catalytic material, a Cu3 (BTC) 2 metal organic framework is used as a substrate, ionic liquid [EMIM] [BF4] is introduced into crystal pore channels, and an ionic liquid modified catalytic material [EMIM] [BF4] (at) Cu3 (BTC) 2 is obtained. The modification of a small amount of ionic liquid avoids the defects of high cost and large viscosity when the ionic liquid is used as an electrolyte, relieves the problems of overhigh reduction potential, competition of hydrogen evolution reaction and the like when a copper-based catalyst is used for electrocatalysis of CO2, and effectively improves the Faraday efficiency of ethylene. The raw materials used in the method are cheap and easy to obtain, and the preparation method is simple and easy to popularize.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of catalytic materials for electrocatalysis of carbon dioxide, and in particular to a preparation and modification method and application of a catalytic material for electrocatalytic reduction of carbon dioxide to ethylene using an ionic liquid-modified Cu-MOF. Background Art

[0002] Since the Industrial Revolution, large amounts of greenhouse gas CO2 have been emitted, causing global warming, sea level rise, land desertification and other natural disasters. CO2 capture, utilization and storage technology is a low-carbon technology that can achieve large-scale CO2 emission reduction while continuing to use fossil energy. Among them, chemical utilization in CO2 utilization technology is currently one of the most attractive ways to reduce emissions. Among CO2 resource utilization technologies, electrocatalytic technology has good prospects due to its advantages such as the use of clean energy and mild reaction process.

[0003] Among the products of CO2 electroreduction, ethylene has a high added value, but its production requires complex multi-electron / proton coupling and carbon-carbon atom (CC) coupling, so the Faraday efficiency is low. Cu is the only metal material that can reduce CO2 to produce C2 and C2+ hydrocarbon compounds. The binding energy of the CO2 intermediate CO* and the adsorbed H* is relatively moderate, which can promote the further coupling of the CO* intermediate to produce C2 or even products with higher C numbers. Metal-organic frameworks have the characteristics of large specific surface area, high porosity and finely adjustable structure. Cu3(BTC)2 is a very representative Cu-based metal-organic framework material, which has been widely studied in CO2 electrocatalysis.

[0004] Ionic liquids have excellent properties such as considerable electrical conductivity, adjustable anions and cations, high solubility for CO2, and a wide electrochemical potential window. Currently, they are mostly used as electrolytes or co-catalysts for CO2 electrocatalysis. Among them, alkyl-substituted imidazolyl ionic liquids are widely studied and applied, but compared with traditional aqueous electrolytes, ionic liquids have higher viscosity and higher cost. Summary of the invention

[0005] In the present invention, suitable ionic liquid is selected to modify Cu3(BTC)2, and the advantages of the ionic liquid are used to make up for the defects of the original catalyst, while avoiding the disadvantages of the ionic liquid when used as an electrolyte.

[0006] In view of the problems of high CO2 reduction potential, difficulty in activation, poor selectivity of target products, low Faraday efficiency, competition of hydrogen evolution reaction, etc. of traditional Cu-based catalysts, the purpose of the present invention is to solve the deficiencies of the prior art, and propose a preparation method and application of Cu-MOF electrocatalytic materials, specifically a modification method of Cu-based catalysts, and describe its preparation method and application in electrocatalysis of carbon dioxide. This new catalyst is based on the characteristics of large specific surface area, high porosity and fine structure adjustment of metal organic frameworks. By introducing ionic liquids that are generally used as electrolytes to modify the copper metal organic framework, the advantages of ionic liquids are utilized while solving the inherent problems of Cu-based catalysts. The modified catalyst shows more excellent catalytic performance for ethylene (at a voltage of -2.04V vs Ag / AgCl), and the Faraday efficiency of ethylene is more than doubled.

[0007] The purpose of the present invention is to provide a method for preparing and modifying a Cu-MOF catalyst for electrocatalytic reduction of carbon dioxide with high ethylene selectivity and the application of other catalysts prepared by the method in electrocatalytic reduction of carbon dioxide.

[0008] The technical solution of the present invention is as follows:

[0009] A method for modifying a Cu-MOF electrocatalytic material comprises the following steps:

[0010] 1) Weigh copper acetate monohydrate and dissolve it in deionized water, mix well to form solution A; weigh trimesic acid and dissolve it in a mixed solution of ethanol and N,N-dimethylformamide, mix well to form solution B; mix solution A and solution B, heat and stir to react, centrifuge the precipitate, wash it with ethanol for multiple times, and move it into a drying oven to dry, so as to obtain a copper organic framework Cu3(BTC)2;

[0011] 2) Weigh the ionic liquid [EMIM][BF4] and dissolve it in acetone, stir to form a homogeneous solution, weigh Cu3(BTC)2 and add it to the solution, transfer the solution to a water bath, stir and heat, centrifuge after completion, wash with ethanol for multiple times, and move to a drying oven to dry to obtain [EMIM][BF4]@Cu3(BTC)2.

[0012] The present invention uses Cu3(BTC)2 as a main catalyst and modifies it by adding ionic liquid [EMIM][BF4] to obtain [EMIM][BF4]@Cu3(BTC)2. The modification of [EMIM][BF4] does not change the crystal form and morphology of Cu3(BTC)2, but the interaction between [EMIM][BF4] and Cu3(BTC)2 changes the electronic environment around Cu, greatly affects the valence distribution of Cu, generates more low-valent Cu, and the modified catalyst has better selectivity for ethylene.

[0013] In the present invention, due to the addition of [EMIM][BF4], the Cu-O bond in Cu3(BTC)2 is weakened, and the content of low-valent Cu increases. Low-valent Cu is beneficial to promote the dimerization of CO* during the reaction process, thereby further generating ethylene.

[0014] In step 1), the molar ratio of trimesic acid to cupric acetate monohydrate is 1:1.4-1.6, wherein the molar ratio of 1:1.5 is optimal, the amount of deionized water used is 15-20 mL, wherein 15 mL is optimal, and the amounts of ethanol and N,N-dimethylformamide used are 7-10 mL each, wherein 7.5 ml is optimal.

[0015] The condition for uniform mixing of solution A is continuous stirring for 30 to 60 minutes, more preferably 30 minutes, and the condition for uniform mixing of solution B is continuous stirring for 30 to 60 minutes, more preferably 30 minutes.

[0016] The heating temperature of the mixed solution is 30-40°C. It is most preferred to place the reactor in a 30°C water bath. The stirring time is 6-8h, and most preferably 6h.

[0017] The precipitate was washed by centrifugation three times, but the number of times was too few and there was still residual solvent.

[0018] Drying conditions: drying at 70-90°C for 8-12 hours. Most preferably, drying at 80°C for 10 hours.

[0019] In step 2), the amount of the ionic liquid [EMIM][BF4] used is: 0.4-0.5g, 0.45g is the best, and too much [EMIM][BF4] will lead to blockage of the Cu-MOF pores.

[0020] The amount of acetone used is 15-20 mL, 15 mL is optimal, which is sufficient to completely dissolve [EMIM][BF4]. The solution is mixed evenly under the condition of continuous stirring for 30 to 40 minutes, more preferably 30 minutes.

[0021] The dosage of Cu3(BTC)2 is 100-120 mg, with 100 mg being the best.

[0022] The mixture is heated to 30-40°C, and the reactor is most preferably placed in a 30°C water bath. The stirring time is 6-8h, and most preferably 6h.

[0023] The precipitate was washed by centrifugation three times, but the number of times was too few and there was still residual solvent.

[0024] Drying conditions: drying at 70-90°C for 8-12 hours. Most preferably, drying at 80°C for 12 hours.

[0025] In the present invention, the catalyst substrate is Cu3(BTC)2, a metal organic framework, which has the characteristics of large specific surface area, high porosity and fine structure adjustment, so it has strong CO2 adsorption and capture ability, can make CO2 more easily enter the active site, and can introduce different active sites to inhibit side reactions. Ionic liquids have excellent properties such as considerable conductivity, adjustable anions and cations, high solubility for CO2, and a wide electrochemical potential window. The cation of [EMIM][BF4] is 1-ethyl-3-methylimidazole, which is a common imidazole group and has been shown to help activate CO2, inhibit hydrogen evolution reaction and promote dimerization of CO*. The anion is tetrafluoroborate, which is a fluorinated alkyl group. Related reports show that ionic liquids with fluorinated alkyl groups have stronger absorption capacity for CO2 than ionic liquids without fluorinated alkyl groups, and the more fluorine atoms there are, the greater the solubility of CO2. Using [EMIM][BF4] as a ligand to modify Cu3(BTC)2 can utilize the advantages of ionic liquids to improve the catalytic performance of the original catalyst and avoid the disadvantages of high cost and high viscosity when ionic liquids are used as electrolytes.

[0026] Compared with the prior art, the present invention has the following advantages:

[0027] 1. The raw materials used are cheap and easy to obtain, the preparation method is simple, the equipment is simple, and it is easy to promote;

[0028] 2. It is a universal method for preparing ionic liquid-modified metal organic frameworks, and can also be used to prepare composite catalysts of other metal organic frameworks modified with different ionic liquids.

[0029] 3. The catalyst prepared by this method does not change the original crystal structure of the metal organic framework. The ionic liquid is mainly embedded in the pores of the crystal, retaining a large number of active sites and showing a high selectivity for ethylene. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 These are the XRD results of Cu3(BTC)2 and [EMIM][BF4]@Cu3(BTC)2.

[0031] Figure 2 FT-IR results of Cu3(BTC)2 and [EMIM][BF4]@Cu3(BTC)2

[0032] Figure 3 SEM (top) and TEM (bottom) results of Cu3(BTC)2 and [EMIM][BF4]@Cu3(BTC)2.

[0033] Figure 4These are the XPS results of Cu3(BTC)2 and [EMIM][BF4]@Cu3(BTC)2.

[0034] Figure 5 These are the N2 adsorption and desorption results of Cu3(BTC)2 and [EMIM][BF4]@Cu3(BTC)2.

[0035] Figure 6 These are the Faraday efficiency results of different products of electrocatalytic CO2 of Cu3(BTC)2 and [EMIM][BF4]@Cu3(BTC)2.

[0036] Figure 7 These are the in-situ Raman test results of Cu3(BTC)2 and [EMIM][BF4]@Cu3(BTC)2. DETAILED DESCRIPTION

[0037] Example 1 (Preparation of ionic liquid modified copper-based catalyst [EMIM][BF4]@Cu3(BTC)2)

[0038] Dissolve 5.25mmol of copper acetate monohydrate in 15mL of deionized water and stir for 30min until a homogeneous solution A is formed. Dissolve 3.5mmol of trimesic acid in a mixed solution of 7.5mL of ethanol and 7.5mL of N,N-dimethylformamide and stir for 30min until a homogeneous solution B is formed. Mix solution A with solution B. Stir the mixed solution at 30℃ for 6h. Centrifuge, wash with ethanol 3 times, and dry at 80℃ for 10h to obtain Cu3(BTC)2.

[0039] 0.45 g of ionic liquid [EMIM][BF4] was dissolved in 15 mL of acetone solution and stirred for 30 min until a homogeneous solution was formed. 100 mg of Cu3(BTC)2 was added to the solution and the resulting mixture was stirred continuously for 6 h at 30 °C. After centrifugation, the mixture was washed with ethanol three times and dried at 80 °C for 12 h to obtain [EMIM][BF4]@Cu3(BTC)2.

[0040] Example 2: (Preparation of ionic liquid modified copper-based catalyst [EMIM][PF6]@Cu3(BTC)2)

[0041] The ionic liquid used in Example 1 was replaced with [EMIM][PF6], and the other conditions remained unchanged to obtain the ionic liquid modified copper-based catalyst [EMIM][PF6]@Cu3(BTC)2.

[0042] Example 3: (Preparation of ionic liquid modified copper-based catalyst [BMIM][BF4]@Cu3(BTC)2)

[0043] The ionic liquid used in Example 1 was replaced with [BMIM][BF4], and the other conditions remained unchanged to obtain the ionic liquid modified copper-based catalyst [BMIM][BF4]@Cu3(BTC)2.

[0044] The XRD results of Cu3(BTC)2 and [EMIM][BF4]@Cu3(BTC)2 are as follows Figure 1 As shown in the figure, the main diffraction peaks of Cu3(BTC)2 are well matched and no impurity peaks appear, indicating that a highly crystalline Cu3(BTC)2 sample has been successfully synthesized. The spectrum of the catalyst modified with ionic liquid shows obvious characteristic peaks consistent with the Cu3(BTC)2 sample, that is, the addition of ionic liquid will not destroy the crystal structure of Cu3(BTC)2.

[0045] The FT-IR results of Cu3(BTC)2 and [EMIM][BF4]@Cu3(BTC)2 are as follows Figure 2 As shown in the figure, Cu3(BTC)2 has been successfully synthesized, and 1167cm -1 The peaks on the left and right correspond to the deformation vibration (δC-H) of the CH in the imidazole ring, 1210 cm -1 The peaks on the left and right correspond to BF4 - The asymmetric vibration of ionic liquid indicates that the ionic liquid has been successfully added.

[0046] SEM (top) and TEM (bottom) results of Cu3(BTC)2 and [EMIM][BF4]@Cu3(BTC)2 are shown in Figure 3 As shown in the figure, the synthesized Cu3(BTC)2 crystals aggregate to form a porous structure, and the addition of ionic liquid does not change the morphology of Cu3(BTC)2.

[0047] The XPS results of Cu3(BTC)2 and [EMIM][BF4]@Cu3(BTC)2 are as follows Figure 4 As shown in the figure, after the addition of ionic liquid, the low-valent Cu content increased significantly, which promoted CC coupling and was beneficial to the production of ethylene.

[0048] The N2 adsorption and desorption results of Cu3(BTC)2 and [EMIM][BF4]@Cu3(BTC)2 are as follows Figure 5 As shown in the figure, after the addition of ionic liquid, the specific surface area of ​​the catalyst decreases and the number of micropores decreases, indicating that the ionic liquid has successfully penetrated into the pores of Cu3(BTC)2.

[0049] The Faraday efficiency results of different products of electrocatalytic CO2 of Cu3(BTC)2 and [EMIM][BF4]@Cu3(BTC)2 are shown in Figure 6As shown in the figure, it can be seen that after the addition of ionic liquid, the Faraday efficiency of ethylene increases significantly.

[0050] The in-situ Raman test results of Cu3(BTC)2 and [EMIM][BF4]@Cu3(BTC)2 are as follows Figure 7 As shown in the figure, after the addition of ionic liquid, 2334cm -1 and 2374cm -1 The peak at 1244 cm corresponds to the consumption of CO2 in the electroreduction process, which increases significantly, indicating that the ionic liquid promotes the adsorption of CO2. -1 The peak corresponds to *OCCOH, which is a key intermediate in CC coupling, indicating that ionic liquids improve the selectivity for ethylene by promoting CC coupling.

Claims

1. A method for preparing and modifying a Cu-MOF electrocatalytic material, characterized in that: The following steps are involved: 1) Weigh copper acetate monohydrate and dissolve it in deionized water, stir it evenly to form solution A; weigh trimesic acid and dissolve it in a mixed solution of ethanol and N,N-dimethylformamide, stir it evenly to form solution B; mix solution A and solution B, react under heating and stirring, and obtain copper metal organic framework Cu3(BTC)2 after post-treatment after the reaction; 2) Weigh the ionic liquid [EMIM][BF4] and dissolve it in acetone, stir to form a homogeneous solution, weigh Cu3(BTC)2 and add it to the solution, transfer the mixture to a water bath, stir and heat, centrifuge after completion, wash, and move to a drying oven to dry to obtain [EMIM][BF4]@Cu3(BTC)2, which is the electrocatalytic material of ionic liquid-modified Cu-MOF.

2. The method for preparing and modifying the Cu-MOF electrocatalytic material according to claim 1, characterized in that: In step 1), the molar ratio of trimesic acid to cupric acetate monohydrate is 1:1.4-1.

6.

3. The method for preparing and modifying the Cu-MOF electrocatalytic material according to claim 1, characterized in that: In step 1), the uniformity of solution A is achieved by continuous stirring for 30 to 60 minutes, and the uniformity of solution B is achieved by continuous stirring for 30 to 60 minutes; The reaction conditions under heating and stirring are: heating temperature is 30-40°C, and stirring is continued for 6-8h.

4. The method for preparing and modifying the Cu-MOF electrocatalytic material according to claim 1, characterized in that: In step 1), the post-treatment includes: centrifuging the precipitate, washing with ethanol, and moving it into a drying oven to dry.

5. The method for preparing and modifying the Cu-MOF electrocatalytic material according to claim 1, characterized in that: In step 1), the drying conditions are: drying at 70-90° C. for 8-12 hours.

6. The method for preparing and modifying the Cu-MOF electrocatalytic material according to claim 1, characterized in that: In step 2), the ratio of the amount of the ionic liquid [EMIM][BF4], acetone and Cu3(BTC)2 is: 0.4-0.5g:15-20mL:100-120mg.

7. The method for preparing and modifying the Cu-MOF electrocatalytic material according to claim 1, characterized in that: In step 2), the stirring condition to form a homogeneous solution is: continuous stirring for 30 to 40 minutes.

8. The method for preparing and modifying the Cu-MOF electrocatalytic material according to claim 1, characterized in that: In step 2), the stirring and heating conditions are: the heating temperature is 30-40° C., and the stirring time is 6-8 h.

9. The method for preparing and modifying the Cu-MOF electrocatalytic material according to claim 1, characterized in that: In step 2), the drying conditions are: drying at 70-90° C. for 7-10 hours.

10. Use of the electrocatalytic material of Cu-MOF modified with ionic liquid prepared by the preparation and modification method according to any one of claims 1 to 9 in the electrocatalytic reduction of CO2 to selectively produce ethylene.

Citation Information

Patent Citations

  • Metal copper complex and application thereof in electrochemical CO2 reduction

    CN113185399A

  • Cu-MOF-based catalyst as well as preparation method and application thereof

    CN118287158A

  • Preparation method and application of ionic liquid functionalized copper-based catalytic material

    CN118407086A